Conditions of formation of pyrrhotite and greigite in sediments of Bakchar deposit, Western Siberia - Maksim Andreevich Rudmin; Aleksey Karpovich Mazurov; Aleksey Sergeevich Ruban; Dmitriy Grigorievich Usoltsev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
Recently the formation of pyrrhotite and greigite is more often linked with sulfate-methane transit zones of modern sediments. The paper considers methane generations as one of the possible ways of forming ferromagnetic iron sulfides in sedimentary rocks of Bakchar deposit. The main aim of the study is to reconstruct the environmental conditions for formation of ferromagnetic sulphides in rocks of the Bakchar deposit for disclosure processes, which occurred in sediments of the ancient epicontinental West Siberian Sea at the PaleoceneEocene boundary and also for interpretation of the high magnetization of these rocks. The methods used in the work: mineralogical (scanning electron microscopy, X-ray diffraction analysis), geophysical (kappametry) and geochemical (X-Ray analysis, ICP-MS) studies of sediments (samples from core) which contain pyrrhotite and greigite to reconstructthe evolution of specific postdepositional processes within the shelf of ancient West-Siberian Sea at Paleocene-Eocene boundary. As a result of the investigation the authors advance the theory of ferromagnetic iron sulfides formation in Bakchar deposit sediments with the upward diffusing methane and limited amount of sulfide ion. This environment was enriched with paleoredox proxies (Mo, U, V) and paleoproductivity proxies (Ba[bio] and P). Sedimentary rocks containing pyrrhotite and greigite are characterized by high values of magnetic susceptibility (more than 80x10-5 SI) that is a useful property to identify analogical rocks in drill cores. Presence of ferromagnetic iron sulfides within sedimentary rocks might be used to detect ancient gas hydrate systems in the Paleocene-Eocene sequences of Western Siberia. Methane emissions within the ancient West Siberian Sea might probably triggering large submarine landslides and affecting the global climate change at the Paleocene-Eocene boundary.